2018
DOI: 10.2144/btn-2018-2004
|View full text |Cite
|
Sign up to set email alerts
|

Protein extraction from human anagen head hairs 1-millimeter or less in total length

Abstract: A simple method for extracting protein from human anagen (i.e., actively growing hair stage) head hairs was developed in this study for cases of limited sample availability and/or studies of specific micro-features within a hair. The distinct feature segments of the hair from one donor were divided lengthwise (i.e., each of ∼200–400 μm) and then pooled for three individual hairs to form a total of eight composite hair samples (i.e., each of ∼1 mm or less in total length). The proteins were extracted, digested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…LOC101120019 —A mutation in a 60S ribosomal protein (L21) has been shown to be involved in hereditary hypotrichosis simplex (HHS), a form of nonsyndromic inherited hair loss disorders (Zhou et al, 2011). 60S ribosomal proteins (L6 and L24) have been shown to be expressed in human anagen hair samples (Carlson et al, 2018). Interestingly, the 60S ribosomal protein L10A has been shown to be expressed in root hairs of Medicago truncatula (Covitz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…LOC101120019 —A mutation in a 60S ribosomal protein (L21) has been shown to be involved in hereditary hypotrichosis simplex (HHS), a form of nonsyndromic inherited hair loss disorders (Zhou et al, 2011). 60S ribosomal proteins (L6 and L24) have been shown to be expressed in human anagen hair samples (Carlson et al, 2018). Interestingly, the 60S ribosomal protein L10A has been shown to be expressed in root hairs of Medicago truncatula (Covitz et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Due to extensive disulfide and isopeptide bonds, hair is an extremely difficult matrix to fully dissolve . Human hair samples of 1 mm length have been analyzed in a previous study aimed at identifying the major proteins observed in such small sample sizes . In the present study, a combination of surfactants, elevated temperatures, and ultrasonication was employed to achieve complete dissolution of single 1‐inch (25 mm) hair segments to identify potential GVPs.…”
mentioning
confidence: 99%
“…A recent publication by Mason et al described protein‐based or GVP‐based human identification from a single hair as short as 1 inch long. Another recent publication by Carlson et al described a sensitive method to extract proteins from 1 millimeter or less in total length of human anagen head hairs and compared the proteins identified from hair shaft and hair root. The effectiveness of this method for detecting GVPs has not yet been determined.…”
mentioning
confidence: 99%